STABILITAS STATIS KAPAL POLE AND LINE KM ALDEIS DI PELABUHAN PERIKANAN AERTEMBAGA BITUNG SULAWESI UTARA - Pangalila, Fransisco PT (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2011)
The uncertainty of ocean conditions, such as currents and waves, affects the maneuver ability and stability of vessel on the water. For this reason, a fishing vessel should fulfil specific prerequisites, such as strong vessel construction, good stability to extreme oceanic conditions, good maneuver ability, and thrust.Â  â€œAldeisâ€ boat has a dimension of 15.50 m long, 2.80 m wide, and 1.10 m deep. Average ratio of those parameters was 5.50 for L/B, 13.05 for L/D and 2.37 for B/D, rspectively.Â  The coefficient values of the boat shape were Cb = 0.54 for Cb, Cp = 0.73 for Cp, 0.74 for C and 0.79 for C3, respectively.Â  The boat possessed a maximum shakes to 140 of the boat slant when the righting arm was at 0.20 m of the center point.